Student Worksheets Based on Science Literacy to Practice Students' Argumentation Skills on Electrolyte and Non-Electrolyte Solution Materials - Sisilia Fil Jannati; Rusmini Rusmini (Universitas Lampung, 2022)
Student Worksheets Based on Science Literacy to Practice Students' Arguing Skills on Electrolyte and Non-Electrolyte Solution Subjects. The purpose of this research is to produce student worksheets in training students' argumentation skills on electrolyte and non-electrolyte solution materials that are feasible from the aspect of validity, practicality, and effectiveness. This research uses the 4D research method (Define, Design, Develop, Disseminate), but is limited to the Develop stage. The validity of the student worksheets in terms of content, presentation, language, and graphic aspects obtained very valid criteria with an average percentage of 87.50%: 89.50%; 88.00%; 85.50%. The practicality of the student worksheets is assessed from the student activity observation sheets during learning and student response questionnaires. Relevant student activities obtained very practical criteria with 92.86% at the first meeting and 90.48% at the second meeting. Student response questionnaires got very practical standards with an average percentage in content, presentation, language, and graphics, respectively 97.33%; 96.80%; 93.33%; and 95.83%. The effectiveness of student worksheets to obtain very effective results can be seen from the increase in learning outcomes on cognitive tests and students' argumentation skills tests with n-gain values of 0.79 and 0.85, which have high interpretations. This result is also supported by the results of the Paired Sample T-Test and obtained a Sig value. (2-Tailed) of 0.000 on cognitive tests and tests of argumentation skills. It means there is an influence in the use of student worksheets developed on the results of cognitive tests and students' argumentation skills. Student worksheets based on scientific literacy are very important to train students' argumentation skills. Keywords: student worksheet, scientific literacy, argumentation skills, electrolyte and non-electrolyte solutions DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.02